AGROFORESTRI KALIWU DI SUMBA: SEBUAH TINJAUAN SOSIOLOGIS - Budiyanto Dwi Prasetyo (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2016)
Agroforestry is one of the popular land management systems in Indonesia. The system helps the farmers to increase agricultural production, social life, and ecological stability. Traditional community in Sumba had been implementing agroforestry for a long time, known as Kaliwu and as a part of the indigenous knowledge. Kaliwu as a system is constructed socially through an intensive interaction between local people and its environment and transmitted from generation to generation. This study aimed to asses sociological aspects in behind Kaliwu practices, which allegedly become key factor the sustainability of this system socially, exist until now. The study was conducted for a year in 2009 in the Waimangura Village, Sumba Island. As social research, data was collected through social survey on 30 respondents, in-depth interview, observation, and literature review. Data was analyzed by using quantitative and qualitative procedures. The results indicated that sociologically, Kaliwu as an authentic knowledge of land management system passed on from generation to generation and constructed along with the socio-historical practices by the local people of Sumba. Social norms (adherence to traditional values, arrangement of labour systems, conflict management) and social institution of farmer group became social factors that play significant role to make kaliwu sustainable.